Anaemia among school‐going adolescents in Burkina Faso: Prevalence and associated factors - Ourohiré Millogo; Ilana R. Cliffer; Yllassa Barry; Idrissa Kouanda; Guillaume Compaore; Dongqing Wang; Ali Sie; Wafaie Fawzi (Maternal and Child Nutrition)
Abstract Adolescence, a stage of growth between 10 and 19 years, is a transitional period of intense cognitive, emotional and physical development. Though iron deficiency is the leading cause of morbidity and mortality among this age group, nutritional interventions targeting adolescents are rare. To inform policy and practice aimed at adolescent health, we established the burden of anaemia among school‐going adolescents in Center West Burkina Faso and investigated the potential explanatory factors. A cross‐sectional survey was conducted between January and March 2021. Blood samples, socio‐demographic, socioeconomic, anthropometric, dietary and water, sanitation and hygiene data from 2947 students aged 10–18 years were collected. Anaemia was determined by the World Health Organization's sex‐ and age‐specific haemoglobin concentrations. χ2 tests and logistic regressions were used to identify factors associated with anaemia. The prevalence of anaemia among adolescents in the sample was 36.2%, including 24.2% mild, 11.6% moderate and 0.4% severe anaemia. Compared to males, females were 19% less likely to have mild anaemia (adjusted Odds Ratio [aOR] = 0.81; 95% confidence intervals [CI]: 0.689, 0.955) but 42% more likely to be moderately or severely anaemic (aOR = 1.42; 95% CI: 1.102, 1.831). Among iron‐rich foods, tamarind (aOR = 0.75; 95% CI: 0.610, 0.929) and pumpkin leaves (aOR = 0.77; 95% CI: 0.605, 0.974) were associated with lower odds of anaemia. Several water, sanitation and hygiene factors were associated with higher haemoglobin, including handwashing after toilet use (β = 0.50; 95% CI: 0.031, 0.966) and tooth brushing twice daily (β = 0.19; 95% CI: 0.030, 0.354). Anaemia among adolescents in Burkina Faso should be addressed with interventions targeting diet, sanitation and hygiene.